On interior regularity of solutions of a class of almost-hypoelliptic equations. Armenian Journal of Mathematics - Ghazaryan, Hayk; Margaryan, Vachagan (Armenian Journal of Mathematics, 2010)
In this paper it is proved that all distributional solutions of the non-degenerate, almost hypoelliptic (hypoelliptic by the one of variables) equation P(D)u = P(D_1,D_2)u = 0 are infinitely differentiable in the certain strip in E^2 under a priori assumption that they and its certain derivatives are square integrable with a certain exponential weight.